2019
DOI: 10.3390/rs11091019
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient and Delay Aware 5G Multi-Tier Network

Abstract: Multi-tier heterogeneous Networks (HetNets) with dense deployment of small cells in 5G networks are expected to effectively meet the ever increasing data traffic demands and offer improved coverage in indoor environments. However, HetNets are raising major concerns to mobile network operators such as complex distributed control plane management, handover management issue, increases latency and increased energy expenditures. Sleep mode implementation in multi-tier 5G networks has proven to be a very good approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Hence, alternative energy efficient solutions are required for the end devices because, in case of any program failure, instant battery replacement is complicated, especially in remote areas [35]. Authors in [90,91] suggested energy efficient approaches for the network side; however, energy efficient solutions for the end devices are also desirable.…”
mentioning
confidence: 99%
“…Hence, alternative energy efficient solutions are required for the end devices because, in case of any program failure, instant battery replacement is complicated, especially in remote areas [35]. Authors in [90,91] suggested energy efficient approaches for the network side; however, energy efficient solutions for the end devices are also desirable.…”
mentioning
confidence: 99%